Serum D-dimer Level in Patients with Acute Leukemia in a Tertiary Care Hospital - Amit, Mohammad Nafees Hussain; Rahman, Mohammad Mizanur; Hossain, Md Liakat; Hasan, Md Rashedul; Ali, Md Haidar; Talukder, Kshitish Chandra; Ullah, AZM Ahsan; Sultana, Mst Siddika (Bangladesh Medical Journal, 2023)
D-dimer is a molecule, formed by the breakdown of excessive fibrin from the activation of coagulation system. Ample evidence suggests that increased activation of coagulation system in patients with acute leukemia (AL) leads to higher D-dimer levels. Considering shortage of evidence in our perspective, the study was designed to observe the D-dimer level in acute leukemia in different morphological types and phases among the patients admitted in a tertiary care hospital. This hospital based cross-sectional study was conducted at the Department of Medicine and Department of Hematology in Dhaka Medical College Hospital, for a period of 6 months following approval of this protocol. Patients with New case (NC) of AL, at complete remission (CR) and in patient’s wither lapsed (R) AL were included in the study. Purposive sampling methods were followed for sample selection. Written informed consents were taken from the all study subjects and ethical issues were ensured. Data were collected by interview using a structured questionnaire. All study population were subjected to details history taking, physical examination and relevant investigations of D-dimer level. Collected data were analyzed by the SPSS version 20.0. Among 50 patients, 58% were males and 42% were females. Mean age was 34±5.6 SD years and the height number of patients (40%) belonged to age group 21-30 years. Three fourth of the patient (76%) had diagnosed as AML and rest of them 24% had ALL. The most common subtype of Acute Myeloblastic Leukemia M3 (AML) was 47, 37% and most common subtype of ALL L2 was 50%. Most of the respondents were found as new case (80%) followed by in decreasing order complete remission case 14% and relapse case 6%. Overall, D-dimer level was 3.69 mg/dl (0.1mg/dl-40 mg/dl), and D-dimer level is slightly higher in AML group than ALL patient (4.26 vs 2.18mg/dl). Moreover, new cases have higher level of D-dimer (4.2 mg/dl) in comparison with complete remission (1.2 mg/dl) or relapse case (2.7 mg/dl). It was also found that APL patients has higher D-dimer level than other form of leukemia. D-dimer level in acute leukaemia patients 3.69 mg/dl. Higher value of AML was found in patients than ALL and increased D-dimer level is also evident in newer case particularly APL. D-dimer level rises in acute leukemia patients. However, further study is recommended with appropriate study design. Bangladesh Med J. 2021 Sept; 51(1): 8-17